A Longitudinal, Observational Analysis of Neuronal Injury Biomarkers in a Case Report of a Patient With Paraneoplastic Anti-CRMP5 Antibody-Associated Transverse Myelitis - Mizenko, Christopher; Bennett, Jeffrey L.; Owens, Gregory; Vollmer, Timothy L.; Piquet, Amanda L. (Frontiers in Neurology, 2021)
Biomarkers are needed to guide therapeutic decision making in autoimmune and paraneoplastic neurologic disorders. Here we describe a case of paraneoplastic collapsing response-mediator protein-5 (CRMP5) transverse myelitis (TM) where plasma neurofilament light (NfL) chain and glial fibrillary protein (GFAP) levels facilitate treatment decisions over a 14-month clinical course. Blood and CSF samples obtained at diagnosis as well as 7 months and 14 months into treatment. At the time of initial diagnosis, both plasma NfL (782.62 pg/mL) and GFAP (283.26 pg/mL) were significantly elevated. Initial treatment was with IV steroids and plasma exchange (PLEX) followed by neuroendocrine tumor removal, chemotherapy, and radiation. After initial improvement with chemotherapy, the patient experienced clinical worsening transient elevation of plasma NfL (103.27 pg/mL and GFAP (211.58 pg/mL) levels. Whole body positron emission tomography PET scan did not demonstrate recurrence of malignancy. Repeat PLEX and rituximab induction resulted in improvements in patient function, neurologic exam, and plasma biomarker levels. To our knowledge, this is the first described longitudinal, prospective analysis of neuronal injury biomarkers and association of clinical treatment outcomes in CRMP5 myelitis. Our findings suggest that clinical improvement correlates with NfL and GFAP concentrations.